1985
DOI: 10.1038/jcbfm.1985.56
|View full text |Cite
|
Sign up to set email alerts
|

Ischemia-Induced Shift of Inhibitory and Excitatory Amino Acids from Intra- to Extracellular Compartments

Abstract: Brain ischemia was induced for 10 or 30 min by clamping the common carotid arteries in rabbits whose vertebral arteries had previously been electrocauterized. EEG and tissue content of high energy phosphates were used to verify the ischemic state and to evaluate the degree of postischemic recovery. Extracellular levels and total contents of amino acids were followed in the hippocampus during ischemia and 4 h of recirculation. At the end of a 30-min ischemic period, GABA had increased 250 times, glutamate 160 t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

17
246
0
3

Year Published

1988
1988
2003
2003

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 658 publications
(266 citation statements)
references
References 32 publications
17
246
0
3
Order By: Relevance
“…Our findings suggest that neuronal somata con tribute significantly to the increased extracellular concentration of glutamate observed during isch emia (Benveniste et al, 1984;Hagberg et al, 1985;Korf et al, 1988;Mitani et al, 1991). In contrast, it appears that glutamate accumulates in glial cells fol lowing glucose deprivation and hypoxia.…”
Section: Discussionmentioning
confidence: 63%
“…Our findings suggest that neuronal somata con tribute significantly to the increased extracellular concentration of glutamate observed during isch emia (Benveniste et al, 1984;Hagberg et al, 1985;Korf et al, 1988;Mitani et al, 1991). In contrast, it appears that glutamate accumulates in glial cells fol lowing glucose deprivation and hypoxia.…”
Section: Discussionmentioning
confidence: 63%
“…Acute cerebral insults such as ischemia and brain trauma are associated with excessive release and extracellular accumulation of the neurotransmitter glutamate (1), leading to persistent activation of glutamate receptors and neurodegeneration (2)(3)(4)(5). The glutamate receptor mediated increase of reactive oxygen species (ROS) (6-8) may be a triggering event in the excitotoxic cell death (9)(10)(11)(12).…”
Section: Introductionmentioning
confidence: 99%
“…The latter two were included because previous studies by others and us have shown that these amines are released after NMDAreceptor stimulation and other insults (4,(39)(40)(41)(42)(43).…”
Section: Introductionmentioning
confidence: 99%
“…Glutamate itself is neu rotoxic when injected into cerebral tissue (Rothman and Olney, 1986). Cerebral ischemia is associated with a massive increase in extracellular glutamate concentrations (Benveniste et aL, 1984;Hagberg et aL, 1985). Destruction of glutamatergic afferent pathways or intracerebral administration of NMDA receptor antagonists can reduce the early ischemic damage to the hippocampus in cerebral ischemia and the neuronal necrosis which is observed sev eral days after a period of cerebral ischemia or se-…”
mentioning
confidence: 99%